Hybrid techniques for myocardial regeneration: state of the art and future perspectives - Kędziora, Anna; Konstanty-Kalandyk, Janusz; Litwinowicz, Radosław; Mazur, Piotr; Kapelak, Bogusław; Piątek, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
Myocardium has a limited proliferative capacity, and adult hearts are considered incapable of regenerating after injury. A significant loss in the viable myocardium eventually diminishes the heart’s ability to contract synchronously, leading to heart failure. Despite the development in interventional and pharmacological treatment for ischemic heart disease and heart failure, there is a significant number of highly symptomatic patients. For these individuals, treatments that stimulate myocardial regeneration can offer alleviation of dyspnea and angina and improvement in quality of life. Stem cells are known to promote neovascularization and endothelial repair. Various stem cell lines have been investigated over the years to establish those with the highest potential to differentiate into cardiomyocytes, including bone marrow-derived mononuclear cells, mesenchymal stromal cells, CD34+, CD133+, endothelial progenitor cells, and adipose-derived mesenchymal stromal cells. Stem cell studies were based on several delivery pathways: infusion into coronary vessels, direct injection into the injured region of the myocardium, and delivery within the novel bioengineered scaffolds. Acellular materials have also been investigated over the years. They demonstrate the therapeutic potential to promote angiogenesis and release of growth factors to improve the restoration of critical components of the extracellular matrix. This review summarizes hybrid cardiac regeneration treatments that combine novel bioengineering techniques with delivery approaches that cardiac surgeons can provide.